Correlation between C-MYC and BAX expression with various Ann Arbor stages in B-cell large cell type of Non-Hodgkin lymphoma - Ariadna Anggi Pasang, - (Ektodermal Displazi Grubu, 2023)
ABSTRACT: Diffuse large B-cell lymphoma (DLBCL) is one of the B-cell large cell types of non-Hodgkin lymphoma (NHL) that has poor prognosis with highly variable clinical course. Various prognostic factors have been proposed to predict this, but the results were variable. C-MYC is a proto-oncogen that can cause overexpression leading to the increased of tumor cells proliferation. BAX is a main proapoptotic member of the BCL-2 family proteins that regulates apoptotic function. The study aimed to analyze correlation of c-MYC and BAX protein with various Ann Arbor stages in B-cell large cell type of NHL. This cross-sectional study was performed on 39 formalin fixed paraffin-embedded tissue of patients diagnosed as B-cell large cell type of NHL during January 2017 - December 2019 in Anatomical Pathology Laboratory at Dr. Soetomo General Hospital, Surabaya. To assess the expression of c-MYC and BAX, the immunohistochemistry examination was performed. Immunoexpression of C-MYC and BAX were evaluated according to the number of positive tumor cells divided by the total number of tumor cells and calculated in percentage. There was no difference in C-MYC (p = 0.877) and BAX (p = 0.093) expression with various Ann Arbor stages in B-cell large cell type of NHL. There was no correlation between c-MYC with BAX expression in various Ann Arbor stages in B-cell large cell type of NHL (rs = 0.206, p = 0.209). This indicated that C-MYC and BAX expression alone could not to be used as parameters to predict the outcome of the B-cell large cell type of NHL via Ann Arbor stages.